2017
DOI: 10.1016/j.clgc.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Renal Medullary Carcinoma and Treatment Outcomes

Abstract: Background Renal medullary carcinoma (RMC) is a rare and aggressive type of kidney cancer that primarily affects young adults with sickle cell trait; outcomes are poor despite treatment. Identifying molecular features of this tumor could provide biologic rationale for novel targeted therapies. The objective was to report on clinical outcomes with systemic therapy and characterize molecular features. Patients and Methods This was a retrospective analysis on 36 patients given a pathologic diagnosis of RMC at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 27 publications
7
37
0
Order By: Relevance
“…There is a high genetic overlap with proximal urothelial cancer [39]. No specific mutations are currently known because of small patient numbers; however, in medullary RCC, loss of SMARCB1 [40] or mutations in the ALK gene have been described [41]. A therapeutically targetable genetic mutation is the amplification of the BCR and ABL genes, known from chronic myeloid leukemia, even if BCR/ABL amplifications are only present in a small number of patients with this subtype [39].…”
Section: Pathology and Molecular Alterationsmentioning
confidence: 99%
“…There is a high genetic overlap with proximal urothelial cancer [39]. No specific mutations are currently known because of small patient numbers; however, in medullary RCC, loss of SMARCB1 [40] or mutations in the ALK gene have been described [41]. A therapeutically targetable genetic mutation is the amplification of the BCR and ABL genes, known from chronic myeloid leukemia, even if BCR/ABL amplifications are only present in a small number of patients with this subtype [39].…”
Section: Pathology and Molecular Alterationsmentioning
confidence: 99%
“…Medullary RCC (mdRCC) occurs in patients with sickle cell hemoglobinopathy . mdRCC is diagnosed with the loss of nuclear staining for the SMARCB1/INI1 tumor suppressor protein , resulting from either loss of heterozygosity (LOH) and balanced translocations or biallelic loss . TFE‐3 or TEF‐B translocation‐associated RCCs (tfeRCCs) exhibit varied histology from clear cell morphology to papillary architecture .…”
Section: Category Two Classification: Molecular Pathologymentioning
confidence: 99%
“…Extending these findings to a larger cohort, Carlo et al . have recently observed SMARCB1 rearrangements by FISH in 8/10 tumors tested, with the remaining cases showing biallelic loss of SMARCB1 …”
Section: Renal Medullary Carcinoma − Towards a Clinical And Molecularmentioning
confidence: 99%
“…31 Extending these findings to a larger cohort, Carlo et al have recently observed SMARCB1 rearrangements by FISH in 8/10 tumors tested, with the remaining cases showing biallelic loss of SMARCB1. 32 In light of the molecular knowledge lent by these recent studies, the question arises as to whether this carcinoma, in an appropriate morphologic context, is more defined by "SMARCB1-opathy" or by the clinical scenario of hemoglobinopathy. In this regard we have recently studied a group of rare tumors that seem to straddle the molecular and clinical criteria for RMC, principally by being morphologically appropriate tumors for an RMC diagnosis, demonstrating loss of SMARCB1 by immunohistochemistry, yet arising in patients where sickle cell trait or disease has been excluded rigorously.…”
Section: Renal Medullary Carcinoma à Towards a Clinical And Molecularmentioning
confidence: 99%